Observation and measurements of the production of prompt and non-prompt J/ψ mesons in association with a Z boson in pp collisions at √s = 8 TeV with the ATLAS detector - Alconada Verzini, María Josefina (2015)
The production of a (Formula presented.) boson in association with a (Formula presented.) meson in proton–proton collisions probes the production mechanisms of quarkonium and heavy flavour in association with vector bosons, and allows studies of multiple parton scattering. Using (Formula presented.) of data collected with the ATLAS experiment at the LHC in (Formula presented.) collisions at (Formula presented.) , the first measurement of associated (Formula presented.) production is presented for both prompt and non-prompt (Formula presented.) production, with both signatures having a significance in excess of (Formula presented.). The inclusive production cross-sections for (Formula presented.) boson production (analysed in (Formula presented.) or (Formula presented.) decay modes) in association with prompt and non-prompt (Formula presented.) are measured relative to the inclusive production rate of (Formula presented.) bosons in the same fiducial volume to be (Formula presented.) and (Formula presented.) respectively. Normalised differential production cross-section ratios are also determined as a function of the (Formula presented.) transverse momentum. The fraction of signal events arising from single and double parton scattering is estimated, and a lower limit of (Formula presented.) at (Formula presented.) confidence level is placed on the effective cross-section regulating double parton interactions.